2020
DOI: 10.1016/j.isci.2020.101075
|View full text |Cite
|
Sign up to set email alerts
|

A Small-Molecule Wnt Mimic Improves Human Limbal Stem Cell Ex Vivo Expansion

Abstract: HIGHLIGHTS MFH-ND is generated by linking a Frizzled inhibitor and an LRP5/6 inhibitor MFH-ND activates the canonical Wnt pathway by oligomerizing Frizzled and LRP5/6 MFH-ND improves the stem cell phenotype of cultivated limbal epithelial cells MFH-ND has therapeutic potential to improve limbal stem cell deficiency treatment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…b. Wnt mimics Because Wnt binds to FZD and LRP5/6 and activates canonical Wnt signaling, it was reasoned that inducing the dimerization of FZD and LRP5/6 should also be able to induce Wnt signaling 14,[34][35][36] . Janda et al first described a hydrophilic Wnt surrogate by linking antagonistic FZD and LRP5/LRP6-binding modules into a single polypeptide chain, in a bispecific binding approach 35 .…”
Section: Activation Of Wnt Signaling Through Wnt Proteins and Wnt Mimics A Wnt Proteinsmentioning
confidence: 99%
See 4 more Smart Citations
“…b. Wnt mimics Because Wnt binds to FZD and LRP5/6 and activates canonical Wnt signaling, it was reasoned that inducing the dimerization of FZD and LRP5/6 should also be able to induce Wnt signaling 14,[34][35][36] . Janda et al first described a hydrophilic Wnt surrogate by linking antagonistic FZD and LRP5/LRP6-binding modules into a single polypeptide chain, in a bispecific binding approach 35 .…”
Section: Activation Of Wnt Signaling Through Wnt Proteins and Wnt Mimics A Wnt Proteinsmentioning
confidence: 99%
“…They were linked by a Gly-Ser polypeptide linker, forcing receptor heterodimerization that phenocopied Wnt/β-catenin signaling in vitro and in vivo, while blocking endogenous Wnt binding 35 . Using this approach, Zhang et al created a Wnt mimics compound by linking a Wnt inhibitor binding to the CRD of FZD (named MFH) to the N-terminal region of DKK that binds to the first β-propeller domain of LRP6 (named ND) through a MFH free carboxyl group and a pentaethylene glycol spacer 14 . They showed that the consolidated compound MFH-ND enhanced Wnt/β-catenin activation and improved the progenitor cell phenotype of cultured limbal epithelial cells in vitro.…”
Section: Activation Of Wnt Signaling Through Wnt Proteins and Wnt Mimics A Wnt Proteinsmentioning
confidence: 99%
See 3 more Smart Citations